Effects of Pt precursors on Pt/CeO2 to water-gas shift (WGS) reaction activity with Langmuir-Hinshelwood model-based kinetics - Park, Yong Min; Son, Minji; Park, Myung June; Bae, Jong Wook (International Journal of Hydrogen Energy, 2020)
The crystallite size effects of Pt nanoparticles on the CeO2 (Pt/CeO2) prepared with four different Pt precursors were investigated in terms of their thermal stability and catalytic activity for a water-gas shift (WGS) reaction using the compositions of reformates after a typical steam reforming of propane. The Pt/CeO2 prepared with a diamine dinitroplatinum (Pt(NO2)2(NH3)3) precursor, which forms the cationic Pt(NH3)22+ species on the negatively-charged CeO2 surfaces, revealed a superior catalytic activity and thermal stability by forming the partially oxidized smaller Pt nanoparticles decorated with metallic Pt surfaces as well as by forming the strongly interacted PtOx-CeO2 interfaces. The stable preservation of the pristine smaller Pt nanoparticles with small aggregations even under the hysteresis test from 250 to 400 °C was mainly attributed to the strong metal-support interactions. The optimized Pt/CeO2 was further studied to obtain kinetic equations derived by Langmuir-Hinshelwood (LH) model, and the optimal operating conditions of WGS reaction were found to be ~280 °C and H2O/CO molar ratio of 9 with the activation energy of ~78.4 kJ/mol.
Keywords: Crystallite size effects; Langmuir-Hinshelwood; Langmuir-Hinshelwood models; Negatively charged; Optimal operating conditions; Steam reforming of propane; Strong metal support interaction; Water gas shift (WGS) reaction; Kinetics; Pt precursors; Pt/CeO2; Syngas; Water-gas shift (WGS) reaction